Volume control : hearing in a deafening world - Owen, David, 1955- (Riverhead Books, 2019)
Our sense of hearing makes it easy to connect with the world and the people around us. The human system for processing sound is a biological marvel, an intricate assembly of delicate membranes, bones, receptor cells, and neurons. Yet many people take their ears for granted, abusing them with loud restaurants, rock concerts, and Q-tips. And then, eventually, most of us start to go deaf.